Cross-Sectional Analysis of the Resistance to the Use of Mobile Money Transfer Services. An Application to the Case of Airtel Congo Customers (Global Journal of Management and Business Research, 2025)
Abstract- This article aims at assessing the impact of moderating factors on behavioral intuition and the use of mobile money technology Using the revised unified theory of acceptance and use of technology as a working basis we selected key constructs and developed a research model to adapt and delve into the question The moderating roles of three sociodemographic factors age gender and marital status are examined Data collection was conducted through a questionnaire submitted to Airtel Congo customers in the Brazzaville department The validation of the research model was carried out using fuzzy set modeling through the totally fuzzy logic operationalized by Cheli and Lemmi 1995 The results obtained in this area including the effective implementation of the completely fuzzy and relative logic and their limitations have been presented To clarify the specific role of moderator factors we compared the value of the fuzzy multidimensional general resistance index of customers calculated without taking into account the moderator factors with that of the fuzzy multidimensional general index estimated after considering these factors The fuzzy multidimensional general resistance index of customers excluding the moderator factors is estimated at 0 475 47 5 of Airtel Congo customers surveyed are moderately resistant to using mobile money transfer services
Keywords: unified theory of acceptance and use of technology; totally fuzzy and relative logic; mobile money transfert; airtel congo